2008
DOI: 10.1007/s10450-007-9091-8
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental studies of gas sorption within mesopores situated amidst an inter-connected, irregular network

Abstract: There has been little, or no, direct testing of theories of gas sorption within particular pores situated amidst a highly inter-connected pore network. The concept of thermodynamically independent pores within networks has also been challenged. In this work, a novel integrated nitrogen sorption and mercury porosimetry technique has been used to deconvolve the condensation and evaporation processes within a specific subset of pores contained within a larger, irregular network. The sizes and geometry of these po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…The key finding from these previous studies (Rigby et al 2008) was that the relative pressure for capillary condensation, in the abstracted pores, was well predicted by the Cohan (1938) equation for a cylindrical meniscus, once the correct t-layer correction, appropriate to the particular degree of geometric and chemical heterogeneity of the surface of S1, had been made. Previous work (Rigby 2007) had suggested that the surface of sol-gel silicas is both chemically and geometrically heterogeneous.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…The key finding from these previous studies (Rigby et al 2008) was that the relative pressure for capillary condensation, in the abstracted pores, was well predicted by the Cohan (1938) equation for a cylindrical meniscus, once the correct t-layer correction, appropriate to the particular degree of geometric and chemical heterogeneity of the surface of S1, had been made. Previous work (Rigby 2007) had suggested that the surface of sol-gel silicas is both chemically and geometrically heterogeneous.…”
Section: Introductionmentioning
confidence: 92%
“…Since, the heterogeneities were macroscopic the 'neck' can be removed from the 'bottle' by fragmentation of the S1 pellets. In previous studies (Rigby et al 2008) of this disordered system, using integrated gas sorption and porosimetry, it was shown (independently of gas sorption) that mercury becomes entrapped within S1, only in those pores with a very narrow range of radii, centered around 7.32 nm. In the integrated experiments, the subtraction of the nitrogen isotherms obtained following mercury entrapment, from the corresponding isotherms obtained beforehand, allowed deconvolution of the changes to the capillary condensation and evaporation processes occurring because of the presence, or lack thereof, of the sub-set of pores that entrap mercury.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations